STATISTICAL ASSESSMENT OF THE AVERAGE YIELDS OF CUCUMBERS AND GHERKINS IN SOME BALKAN COUNTRIES - Delyana DIMOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Data concerning harvested area and production of cucumbers and gherkins have been extracted from the website of FAOSTAT. They have been presented and saved in a separate Excel file. The calculated average yields of the indicated crops in five Balkan countries (Greece, Romania, North Macedonia, Albania and Bulgaria) have been studied in the period 1999-2020. The mentioned information has been compared, assessed and summarized. Analysis of variance and Tukey's range test have been applied to the considered data about average yields. The results showed that the indicator (harvested area) for these two crops had significantly bigger values for Romania in the interval from 2001 to 2020. At the same time, the values of the other examined indicator (average yields) for Greece were relatively higher during 2014 as well as 2018. A similar situation was observed for Romania in 2004, 2008 and 2018, while for Bulgaria in the two years - 2014 and 2016. This indicator for Albania and North Macedonia increased gradually during the bigger part of the period. The statistical evaluation of the average yields of cucumbers and gherkins for the studied Balkan countries formed three groups with statistically significant differences.